Market for Information and Selling Mechanisms - David Bounie; Antoine Dubus; Patrick Waelbroeck (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We investigate the strategies of a data intermediary selling consumer information to firms for price discrimination purpose. We analyze how the mechanism through which the data intermediary sells information influences how much consumer information she will collect and sell to firms, and how it impacts consumer surplus. We consider three selling mechanisms tailored to sell consumer information: take it or leave it, sequential bargaining, and auctions. We show that the more information the intermediary collects, the lower consumer surplus. Consumer information collection is minimized, and consumer surplus maximized under the take it or leave it mechanism, which is the least profitable mechanism for the intermediary. We discuss two regulatory tools – a data minimization principle and a price cap – that can be used by data protection agencies and competition authorities to limit consumer information collection, increase consumer surplus, and ensure a fair access to information to firms.
Keywords: 330; market for information; competition; price discrimination; data collection; privacy; selling mechanisms